Regulation of LC3-Dependent Protective Autophagy in Ovarian Cancer Cells by Protein Phosphatase 2A. Issue 4 (1st May 2013) - Yin, Xia; Zhang, Ning; Di, Wen
Abstract : Objective: Protein phosphatase 2A (PP2A) is a target for cisplatin, which is a widely used platinum drug to treat various cancer, including ovarian cancer. However, to date, the exact role of PP2A in chemoresistance to cisplatin-centered ovarian cancer therapy is not clear. Methods and Materials: To analyze the function of PP2A in cisplatin-resistant ovarian cancer cells, we derived A2780/cisplatin (CDDP), which is resistant to cisplatin, from A2780 cell line. Western blotting was used to detect the expression of PP2A, autophagy, and apoptosis markers. Results: The expression of PP2A catalytic subunit, (PP2Ac) was reduced in A2780/CDDP as well as in cisplatin-resistant patients' tissues compared with A2780 and cisplatin-sensitive patients. In the A2780 cells, cisplatin induced both apoptosis and autophagy. Interestingly, however, the autophagy inhibitor 3-methyladenine increased the cell death induced by diamindichloridoplatin (DDP), which suggested the protective function of autophagy in DDP-induced cell death. Knocking down of PP2A promoted autophagy but suppressed DDP-induced apoptosis and cell death. In contrast, overexpression of PP2Ac or reinduction of the activity of PP2A by FTY720 decreased autophagy but increased cell death induced by DDP. Our experiments demonstrated that apoptosis suppressed by the knocking down of PP2Ac can be reversed by the administration of 3-methyladenine. The elevated accumulation of microtubule-associated protein 1 light chain 3-II and the decline of the autophagy substrate p62 were also observed in PP2Ac–small interfering RNA transfected cells. However, overexpression of PP2Ac suppressed the accumulation of microtubule-associated protein 1 light chain 3-II and restored p62. Conclusions: Taken together, our results showed that protective autophagy regulated by PP2Ac is at least part of the mechanism to how certain ovarian cancers are resistant to cisplatin. Prospective studies are necessary to determine the detailed mechanism of how PP2Ac regulates autophagy in chemoresistant patients.